UTILIZACION DE LA AMALGAMA EN LA ODONTOPEDIATRIA ACTUAL - Velásquez Reyes, Víctor (1999)
This work we 'll try to show the most recent opinions about dental amalgam 's benefits and/or disadvantages when used as a dental restorative material. We '11 analiza the literature regarding the great controversy that mercury contained in amalgams has provoked the lasts years.